If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -9x = 51 + -2x Solving 13 + -9x = 51 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 13 + -9x + 2x = 51 + -2x + 2x Combine like terms: -9x + 2x = -7x 13 + -7x = 51 + -2x + 2x Combine like terms: -2x + 2x = 0 13 + -7x = 51 + 0 13 + -7x = 51 Add '-13' to each side of the equation. 13 + -13 + -7x = 51 + -13 Combine like terms: 13 + -13 = 0 0 + -7x = 51 + -13 -7x = 51 + -13 Combine like terms: 51 + -13 = 38 -7x = 38 Divide each side by '-7'. x = -5.428571429 Simplifying x = -5.428571429
| 7a+9b= | | 3(a-2)+5w=22 | | 2x^3+5x^2-12=0 | | -19-9x=10x+23 | | 3m+4-9m=-9-6m+23 | | 16x-8=14x+4 | | 3(3+6x)-3=114 | | 6-68= | | 68-6= | | 5x+2(6x-8)=120 | | 17.92=x-0.2x | | 35e+23-30e=48 | | 4(3x-3)=24 | | 13-6x=3x+24 | | 5z-6=x | | 1+2x=9+3x | | -w^2-3w-7=-2w^2+3 | | 37-3x+10x=2 | | 2(3x-5)=7(x-2) | | 48x^2-84x+36=0 | | 6xd=24 | | 4a-(a+6)=12 | | 11-5x=-7x-15 | | 4a+1+-a=19 | | 12-x-5x=-198 | | 6x-2=10x-10 | | 7p-5-6p=8 | | 2x+3=3(x+8) | | y+2-x= | | 3x+2(x-4)=-23 | | -3(u+7)=-18 | | 6a+42-2a=50 |